Factors contributing to elder abuse in Ethiopia. Issue 2 (13th April 2015) - Chane, Samson; Adamek, Margaret E.
Abstract : Purpose: – The purpose of this paper is to increase understanding of elder abuse in Ethiopia by considering the perspectives of abused elders. Design/methodology/approach: – A phenomenological study was conducted to investigate the lived experience of 15 elders (six men, nine women) in Ethiopia who experienced domestic abuse. Data were collected using unstructured interviews and were analyzed using interpretive phenomenological analysis. The results described here focus on Ethiopian elders' perceptions of factors contributing to abuse. Findings: – Themes identified in elders' statements about the factors contributing to elder abuse included: declining respect for elders, conflicts of interest, poor health, mutual dependency and other economic issues, and loss of support providers. Abject poverty was evident as an underlying influence contributing to abuse. One elder stated, "Life is meaningless without food and without a caregiver. I am ready to welcome death." Research limitations/implications: – Documentation of elder abuse is needed to bring recognition to abuse as a problem deserving public attention and response. Practical implications: – Given the apparent influence of poverty-related factors on the occurrence of elder abuse among the study's participants, policy initiatives are needed to enhance the economic well-being of older adults in Ethiopia. Originality/value: – Since elder abuse is generally not viewed as a societal problem in Ethiopia, there have been very few studies documenting its existence. Research on elder abuse in Ethiopia and other developing nations can help to bring the issue to the attention of communities and authorities.